Robotic excision of paraesophageal bronchogenic cyst in a 9-year-old child - Belal Bin Asaf; Arvind Kumar; C L Vijay (Wolters Kluwer Medknow Publications, 2015)
Bronchogenic cysts are often asymptomatic and discovered as an incidental finding. They may become symptomatic due to esophageal compression as they increase in size or from development of infection. We report a case of a 9-year-old male with an asymptomatic bronchogenic cyst who underwent successful robotic assisted thoracoscopic excision.